CGIAR Climate Change, Agriculture and Food Security Program Theme 3: Pro-Poor Climate Change Mitigation Currently Named: Theme 3: Low Emissions Agriculture. Evaluation of 2011-2013 - Smith, Gordon R.; Ecofor LLC (2014)
This document is an evaluation of a component of the CGIAR research program “Climate Change, Agriculture and Food Security” (CCAFS), specifically the program “Pro-poor climate change mitigation” which CCAFS has labeled “Theme 3” and since renamed “Low emissions agriculture.” This evaluation addresses CCAFS Theme 3, from years 2011-13. CCAFS specified that the evaluation will use six criteria: 1. Relevance: Is the Theme 3 program being managed in line with vision in the Program Plan and Theory of Change, and CGIAR reform process, including cross center research, working with partners and consulting with stakeholders in designing research? 2. Effectiveness: How successful is program management at guiding program work to serve program goals, include synergies across activities , involving regional programs, working across scales, and addressing situations that are not going according to plan? 3. Efficiency: Are administrative and transaction costs reasonable? 4. Impact: Are outcomes and incipient outcomes sufficient for a US $10 million per year program? Is low emission development occurring in land use in regions where CCAFS is working? Are women and marginalized groups benefiting? 5. Sustainability of Benefits: Are impacts likely to have continuing benefit for a long time? 6. Quality of Science: For the amount of funding of the program, are there enough high quality publications, and publications in high impact journals?